Game Edukasi Untuk Menghafal Al-Quran Secara Sederhana Menggunakan Game Development Kit - Sopiyan Dalis; Heri Kuswara; Muhammad Idrus; Syamsul Bahri (LPPM Universitas Bina Sarana Informatika, 2022)
The Covid-19 pandemic has greatly impacted various aspects around the world, the education aspect has not escaped attention, forcing students and workers to do activities at home. And most students (especially Islamic schools) who when they enter school are memorizing the Al-Quran forget to return when they return to school. This is very unfortunate considering the virtue of memorizing the Qur'an is very great reward and also the goodness in it. Various methods are also widely used by parents and teachers, including through learning media in the form of games. Education Game